The Role of PT. Permodalan Nasional Madani (PNM) Mekaar Syariah in Increasing the Income of Housewives of Ultra Micro Businesses (UMi) - Demila, Demila; Sundari, Sundari (Danadyaksa: Post Modern Economy Journal, 2023)
Indonesia’s economic category in 2020 shows that the lower middle economic level reached 78%. Ultra micro business is a business run by the lowest level of business actors, where many of these positions are occupied by women, the percentage reaches 95% and 5% is achieved by men. Lack of public understanding of business education and the lack of business capital, PT. Permodalan Nasional Madani is present as one of the institutions that provides facilities through the Mekaar Syariah program in an effort to increase the family income of ultra-micro business actors. This research aims to determine the role of PT. Permodalan Nasional Madani’s Mekaar Syariah program in increasing the income of ultra-micro business owners. This research is a type of qualitative research with a case study approach and is descriptive in nature. The data sources taken are primary and secondary data sources. The data collection techniques used in this research are observation, interviews, and documentation. The role of PT. PNM Mekaar Syariah has been trusted by customers to increase the income of Ultra Micro business actors through the capital provision program provided. This is proven by customer continuity in financing.